Analisis Perilaku Prososial Melalui Teori Kognitif Sosial pada Anak-Anak Yatim Piatu di LKSA Mambaul Ulum Jember - Febiani Bella Rizqita (Fakultas Dakwah UIN KHAS Jember, 2022)
Humans are born as individual and social beings. They cannot be separated from social life because fundamentally they need each other. However, some believe that they are capable of living independently without the help of others. Whereas, it is clear in the Qur'an that they must help each other in the path of truth. Therefore, the importance of prosocial behavior should be instilled in children from an early age so that they can socialize well in their environment. The focus of the research in this thesis is 1) How is prosocial behavior in orphaned children through social cognitive theory at LKSA Mambaul Ulum Jember? 2) How is the process of forming prosocial behavior through social cognitive theory in orphaned children at LKSA Mambaul Ulum Jember? The method used in this research is a qualitative research method, with the type of research used being a case study. Data collection techniques used are interviews, observations, and documentation. This study concludes that 1) Prosocial behavior in orphaned children at LKSA Mambaul Ulum is categorized as good, seen from the social cognitive theory approach, the subjects are able to imitate and choose positive behavior from adult behavior which later enables them to display good behavior in accordance with social norms. 2) The process of forming prosocial behavior in orphaned children at LKSA Mambaul Ulum Jember starts from observation and imitation of the behavior of caregivers and adults, then they filter the information they receive, and the process of choosing good and bad behavior in each subject is different according to their thinking.